• Matéria: Matemática
  • Autor: rafaelabalduinorosa
  • Perguntado 6 anos atrás

a) (+).(+) = b) (+).(-) = c)(-).(-) = d) (-).(+) = e) (+).(+).(+) = f) (+). (-).(-) = g) (-).(+).(+) = h) (-).(-).(-) = i) (-).(+).(-).(+) = j) (-).(-).(-).(-) = k) (-).(-).(-).(+).(+) = I) (-).(-).(-).(-).(-) = m) (-).(+).(+).(+).(-) = n) (-).(+).(-).(+).(-) =

Respostas

respondido por: luka0001
2

Explicação passo-a-passo:

a) +

b) -

c) +

d) -

e) +

f) +

g) -

h) -

i) +

j) +

k) -

l) -

m) +

n) -

Perguntas similares